PPEylation of proteins: Synthesis, activity, and stability of myoglobin-polyphosphoester conjugates. (November 2018) - Pelosi, Chiara; Duce, Celia; Russo, Daniela; Tiné, Maria Rosaria; Wurm, Frederik R.
Graphical abstract: Highlights: Protein-polymer conjugation with biodegradable polymers. Multiple technique approach for the protein conjugate's characterization. Proteins still folded and active in physiological conditions after bioconjugation. Trend between the properties of the conjugates and the polymer molar mass. Abstract: Protein-polymer conjugates are used to treat several diseases. PEGylation, i.e. the modification with poly(ethylene glycol) (PEG) is the currently used strategy. However, due to its non-biodegradability, the design of effective and degradable conjugates is of both academic and industry potential. We present the preparation and studies of the activity and stability of novel biodegradable myoglobin-polyphosphoester conjugates. Poly(ethyl ethylene phosphate) (PEEP) is a water-soluble polyphosphoester, which had been reported to be biocompatible and biodegradable. PEEP is a promising candidate as a degradable substitute for the "gold standard" PEG, which can cause long-term effects, as it is not degradable. PEEPylated conjugates with a variable degree of polymer grafting were synthesized, characterized (with online triple detection size exclusion chromatography, mass spectrometry, and gel electrophoresis), and compared with PEGylated analogs. We highlight differences in how the structure, the number, and the length of the polymer influence the properties of the conjugates. Overall, the analyses conducted (including activity assay, calorimetry, and fluorimetry measurements) show that the covalent attachment of the polymer does not irrevocably affect the protein's features under physiological conditions, suggesting the potential of this new class of polymers for the design of a new generation of fully degradable conjugates.